The effects of oral administration of Cola nitida on the pharmacokinetic profile of metoclopramide in rabbits - Cecilia Nwadiuto Amadi; Wisdom Izuchukwu Nwachukwu (BMC, 2020)
Abstract Background Cola nitida is commonly chewed in many West African cultures to ease hunger pangs and sometimes for their stimulant and euphoriant qualities. Metoclopramide is a known substrate for P-gp, SULT2A1 and CYP2D6 and studies have revealed that caffeine- a major component of Cola nitida can induce P-glycoprotein (P-gp), SULT2A1 and SULT1A1, hence a possible drug interaction may occur on co-administration. The aim of this study was to investigate the pharmacokinetic interactions of Cola nitida and metoclopramide in rabbits. Methods The study was performed in two stages using five healthy male rabbits with a 1-week washout period between treatments. Stage one involved oral administration of metoclopramide (0.5 mg/kg) alone while in the second stage, metoclopramide (0.5 mg/kg) was administered concurrently with Cola nitida (0.7 mg/kg). Blood samples were collected after each stage at predetermined intervals and analyzed for plasma metoclopramide concentration using HPLC. Results Compared with control, the metoclopramide/Cola nitida co-administration produced a decrease in plasma concentration of metoclopramide at all the time intervals except at the 7th hour. The following pharmacokinetic parameters were also decreased: area under the curve (51%), peak plasma concentration (39%), half-life (51%); while an increase in elimination rate constant (113%) and clearance rate (98%) were noted indicating rapid elimination of the drug. A minimal decrease in absorption rate (10%) was also observed. Conclusions The results of this study reveal a possible herb-drug interaction between Cola nitida and metoclopramide.